A New Two Switched-Impedance Network for High Ratio Quasi-Z-Source Inverter - Irham Fadlika; Mega Agustina; Rahmatullah Aji Prabowo; Misbahul Munir; Arif Nur Afandi (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
The increasing demand and widespread of renewable energy inherently compel the development of power electronics converter as an interface between consumers and the energy source/s. This paper presents a new two switched-impedance networks qZSI converter called High Ratio Two Switched-impedance quasi-Z-Source Inverter (HR2SZ-qZSI). Compared with the previous topology, this proposed HR2SZ-qZSI topology can achieve higher voltage gain with lower shoot-through duty ratio, and a higher boost factor. This paper also discusses comparative analysis between the previous topology and the proposed HR2SZ-qZSI topology. Furthermore, the simulation and experimental data are presented to prove the theoretical analysis of the proposed HR2SZ-qZSI topology. Despite the additional components needed, it accentuates that this proposed converter retains all features of qZSI: common ground point between the dc source and converter and smooth input current operation. Furthermore, almost all the devices rating including capacitor and diode voltage, and inductor current ripple are lower than the preceding relevant two switched-impedance qZSI family. Accordingly, this proposed HR2SZ-qZSI clearly a good power conditioning alternative for renewable generation system.